PJMHS 2022
DOI: 10.53350/pjmhs20221611158
|View full text |Cite
|
Sign up to set email alerts
|

Association between TIMI Risk Score and in-Hospital Mortality in Acute STEMI Patients Undergoing Primary PCI

Abstract: Aim: To determine the association between TIMI risk score and in-hospital mortality and adverse events in acute STEMI patients undergoing primary PCI at a tertiary cardiac care facility. Study design: Retrospective study. Place and duration of study: Catheterization Laboratory of Cardiology Unit, Dr. Ruth KM Pfau, Civil Hospital Karachi from 1st October 2017 to 31st March 2019. Methods: Three hundred and sixty six acute STEMI patients who admitted through emergency and underwent primary angioplasty were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Regarding risk scores, Sato et al [10] showed that higher GRACE risk scores were shown to be strongly related with an increased risk of in-hospital mortality and MACE; as in-hospital MACE occurred in 193 patients (75.7%) of high GRACE score group vs. 53 patients (19.1%) and 16 patients (5.8%) of intermediate and low GRACE RS groups respectively with p-value < 0.001. Again, Shah et al [19] found that higher TIMI score had increased the mortality rates with in-hospital death occurred in 4 patients (1.1%) with TIMI RS= 5 and increased in patients with TIMI RS= 10 and 11 to 5 patients (1.5%) for each, with p value < 0.001.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding risk scores, Sato et al [10] showed that higher GRACE risk scores were shown to be strongly related with an increased risk of in-hospital mortality and MACE; as in-hospital MACE occurred in 193 patients (75.7%) of high GRACE score group vs. 53 patients (19.1%) and 16 patients (5.8%) of intermediate and low GRACE RS groups respectively with p-value < 0.001. Again, Shah et al [19] found that higher TIMI score had increased the mortality rates with in-hospital death occurred in 4 patients (1.1%) with TIMI RS= 5 and increased in patients with TIMI RS= 10 and 11 to 5 patients (1.5%) for each, with p value < 0.001.…”
Section: Discussionmentioning
confidence: 95%